2016
DOI: 10.1038/srep36711
|View full text |Cite
|
Sign up to set email alerts
|

Random mutagenesis of the hyperthermophilic archaeon Pyrococcus furiosus using in vitro mariner transposition and natural transformation

Abstract: Transposition mutagenesis is a powerful tool to identify the function of genes, reveal essential genes and generally to unravel the genetic basis of living organisms. However, transposon-mediated mutagenesis has only been successfully applied to a limited number of archaeal species and has never been reported in Thermococcales. Here, we report random insertion mutagenesis in the hyperthermophilic archaeon Pyrococcus furiosus. The strategy takes advantage of the natural transformability of derivatives of the P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Meanwhile, random mutagenesis based on homologous recombination of a transposon-inserted genomic DNA library, prepared by in vitro transposition using hyperactive transposases, was reported for mesophilic pathogens Haemophilus influenzae and Streptococcus pneumoniae to determine the set of essential genes (34). This strategy was recently applied for the extremely thermophilic bacterium Thermus thermophilus (35) and hyperthermophilic archaeon P. furiosus (36), although the phenotypic screening from the mutant library has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, random mutagenesis based on homologous recombination of a transposon-inserted genomic DNA library, prepared by in vitro transposition using hyperactive transposases, was reported for mesophilic pathogens Haemophilus influenzae and Streptococcus pneumoniae to determine the set of essential genes (34). This strategy was recently applied for the extremely thermophilic bacterium Thermus thermophilus (35) and hyperthermophilic archaeon P. furiosus (36), although the phenotypic screening from the mutant library has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…As a mechanism of horizontal gene transfer, it may allow bacteria to acquire new genes to better adapt to their environment. More than 65 species of both Gram-negative and Gram-positive bacteria, and some archaea, are known to be naturally competent, expressing protein complexes that span all cellular compartments to acquire exogenous DNA and transport it into the cell for recombination with the chromosome (1,2).…”
mentioning
confidence: 99%
“…, if the mutant allele is converted against the wild-type allele, the abundance (copies) of the mutant allele will be eliminated and that of the wild-type allele will be increased, and the reverse is also true (Khakhlova and Bock 2006; Soppa 2011). In polyploid archaea, allele equalization among the multiple genome copies via gene conversion has been repeatedly demonstrated (Hildenbrand et al 2011; Lange et al 2011; Guschinskaya et al 2016). For instance, Lange et al (2011) showed that in Haloferax volcanii , the heterozygous strain leuB /Δ leuB :: trpA would convert to homozygous leuB or Δ leuB :: trpA strain.…”
Section: Discussionmentioning
confidence: 99%